Rational Combination of Capital Mining and Construction Mining Operations in Coal Cuts - Igorevich Fomin, Sergey; Viktorovich Ivanov, Vladimir; Ngoc Hoan, Do (International Journal of Engineering and Technology, 2018)
The purpose of the construction of a coal open-cut should be an achievement in the shortest possible time of an access to the mineral deposit and creation of favorable mining conditions for achieving the specified performance. In the con-text of investment restrictions during the construction of the mine, the volume of preparatory work should be minimized (preparation of the surface of the quarry field, organization of the field drainage system, creation of a system of tracks, construction of installation sites, power lines, electrical substations, warehouses, and other infrastructure facilities). The main reason for the failure to comply with the deadlines for the commissioning of coal mines is the un-preparedness of the mining front, so the priority in determining the sequence of putting infrastructure facilities into operation is their influence on the development of the mining front. Justification of the sequence of input of mining sites in the development should be carried out based on the analysis of mining and geological conditions, as well as take into account the location of mining sites relative to the systems of transport and energy communications. The creation of the necessary infrastructure should be carried out in stages with the transfer of costs to the later periods of operation of the mine, when conditions for reinvestment from the company’s profits will be created.